Sustainability of Fashion Apparel Toward Environmental Well-Being and Sustainable Development - SHAFIE, SHARIFAH BINTI; Kamis, Arasinah; Ramli, Muhamad Firdaus (Journal of Vocational Education Studies, 2021)
This paper will look into the agenda of the United Nations (UN) for the planned global, social and environmental progression in Sustainable Development Goals (SDGs), especially goals on the quality of education and responsible consumption and production. The combination of these two goals touched on quality education in the field of fashion and also fostered a responsible attitude among producers and consumers. Hence, educators, designers and manufacturers need to ensure the process and production of eco-friendly products do not harm consumers and nature while reducing the amount of waste. Responsibilities of the manufacturers are in terms of producing and adopting sustainable methods in production of textile and clothing products. Furthermore, consumer attitudes and behaviors are also very influential in utilizing of textile products considering the environmental sustainability aspects. In this study, critical review of relevant literature will be conducted. In the context of education for fashion conservation, it is important to raise awareness on the responsibilities of educators, students, consumers and producers on the importance of conserving the environment for future generations. All parties need to play their role in realizing the aspirations of the SDGs agenda. This aspiration can be achieved in an integrated manner through a combination of sustainable practices, positive attitudes and behaviors.